Breast Cancer Patients’ Experiences Undergoing Radiotherapy: A Qualitative Study - Fahrizal Alwi; Mery Silvia Harahap; Winingsih Frihafni; Siti Marlina; Rini Debora Silalahi; Nur Mala Sari; Megawati Sinambela; Meta Rosaulina; Hien Thi Nguyen; Shujen Chen (Jurnal Berita Ilmu Keperawatan, 2026)
Breast cancer is a chronic condition that often requires long-term treatment, including radiotherapy, which may affect patients physically, psychologically, socially, and spiritually. Although previous studies have documented the side effects of radiotherapy, limited evidence exists regarding the lived experiences of breast cancer. This study aimed to explore the lived experiences of women with breast cancer undergoing radiotherapy. A qualitative study with a phenomenological approach was conducted. Ten women diagnosed with breast cancer who had undergone at least five sessions of radiotherapy and were able to communicate their experiences were purposively recruited. Data were collected through semi-structured, in-depth interviews and supported by field notes. Interviews were audio-recorded, transcribed verbatim, and analyzed using the Colaizzi method to identify significant statements, formulate meanings, cluster themes, and describe the essential structure of the participants' lived experiences. The essence of the participants' lived experiences reflected a journey from fear and uncertainty toward acceptance and hope, supported by interpersonal relationships and spirituality. This experience was expressed through six interconnected themes: (1) initial perceptions of radiotherapy, (2) perceived physical and emotional impacts, (3) challenges during treatment, (4) coping strategies, (5) social support throughout the treatment process, and (6) motivation and expectations for recovery. Participants described radiotherapy as a complex experience involving fear, uncertainty, physical discomfort, and emotional distress, while gradually developing resilience through family support, compassionate healthcare providers, adaptive coping strategies, and spiritual beliefs. The findings demonstrate that the lived experiences of breast cancer patients undergoing radiotherapy are multidimensional, highlighting the importance of holistic, patient-centered care that addresses physical, psychological, social, and spiritual needs. Clinical interventions should strengthen therapeutic communication, facilitate family involvement, provide spiritual support according to patients' beliefs and preferences, and promote adaptive coping throughout radiotherapy. Future studies are recommended to employ quantitative or mixed-methods approaches to further examine the relationships among patient experiences, coping strategies, social support, spiritual well-being, and quality of life.